Makeup artistry for film and television : your tools for success on-set and behind-the-scenes - Sciortino, Christine (Routledge, 2021)
"In this comprehensive handbook, author, makeup artist, and educator Christine Sciortino offers a detailed introduction to the conceptual foundations, techniques, and on-set practices of the makeup design process, going beyond technique-centered makeup education to provide an in-depth look at the workings of the film and television world. Through personal stories, interviews, demonstrations, and insights from Sciortino and her colleagues, this book explores the business of makeup artistry, including tailoring a resume, building a kit, self-marketing, breaking down a script, researching and creating makeup looks, working as part of a production team, and different ways to get paid. It further delves into on-set procedures and theory such as anatomy, skin science, color theory, and lighting design. With high-quality step-by-step photo tutorials, this book will help readers to learn and hone techniques for beauty makeup, character makeup, and light special effects including aging and dirtying, grooming, bruises and prosthetics, tattoos, and more. An emphasis is placed on working with actors of all ages, skin tones, and gender identities. This approachable and engaging blend of practical techniques and professional practice is ideal for both introductory-level and established artists. An online resource also offers downloadable templates and sample paperwork for on-set use and practice"--